Clinical history and management recommendations of the smooth muscle dysfunction syndrome due to ACTA2 arginine 179 alterations. (October 2018) - Regalado, Ellen; Mellor-Crummey, Lauren; De Backer, Julie; Braverman, Alan; Ades, Lesley; Benedict, Susan; Bradley, Timothy; Brickner, M; Chatfield, Kathryn; Child, Anne; Feist, Cori; Holmes, Kathryn; et al.
Abstract Purpose Smooth muscle dysfunction syndrome (SMDS) due to heterozygousACTA2 arginine 179 alterations is characterized by patent ductus arteriosus, vasculopathy (aneurysm and occlusive lesions), pulmonary arterial hypertension, and other complications in smooth muscle–dependent organs. We sought to define the clinical history of SMDS to develop recommendations for evaluation and management. Methods Medical records of 33 patients with SMDS (median age 12 years) were abstracted and analyzed. Results All patients had congenital mydriasis and related pupillary abnormalities at birth and presented in infancy with a patent ductus arteriosus or aortopulmonary window. Patients had cerebrovascular disease characterized by small vessel disease (hyperintense periventricular white matter lesions; 95%), intracranial artery stenosis (77%), ischemic strokes (27%), and seizures (18%). Twelve (36%) patients had thoracic aortic aneurysm repair or dissection at median age of 14 years and aortic disease was fully penetrant by the age of 25 years. Three (9%) patients had axillary artery aneurysms complicated by thromboembolic episodes. Nine patients died between the ages of 0.5 and 32 years due to aortic, pulmonary, or stroke complications, or unknown causes. Conclusion Based on these data, recommendations are provided for the surveillance and management of SMDS to help prevent early-onset life-threatening complications.